Methods for Upgrading Specialized On-Board Computers of Military Equipment - Andriі Golovynskyi; Nataliia Kravchenko; Andriі Malenko (Кібернетика та комп'ютерні технології)
Introduction. The problem of modernizing special onboard electronic machines of military equipment became relevant in 2014 with the start of the anti-terrorist operation in Ukraine. Modernization of specialized onboard computers of military equipment is a complex and multi-stage process, which includes updating hardware and software, as well as integrating new technologies. The purpose. Modernization of on-board computers allows to significantly increase the efficiency, safety and combat capability of military equipment, as well as extend its service life. Using modern electronic components and applying modernization methods, it is possible to significantly reduce the size, increase the reliability and productivity characteristics. Results. Such modernization methods as hardware and software upgrades, integration of new technologies, increasing reliability and survivability, ensuring interoperability, updating testing and diagnostic tools, etc. allow for the gradual modernization of weapons models by increasing reliability and adding modern communication methods. Conclusions. The modernization of the 1B57 computer was made without Russian components, and the size, weight and power consumption of the system were significantly reduced. The achieved results can be extended to other weapons models that do not contain the 1B57 computer. However, for them you will have to go all the way from the beginning, from studying the documentation, the circuitry and principles of operation of the computer.